Methoxy-substituted copper complexes as possible redox mediators in dye-sensitized solar cells - Giordano, Marco; Volpi, Giorgio; Bonomo, Matteo; Mariani, Paolo; Garino, Claudio; Viscardi, Guido (New journal of chemistry, 2021)
Three aromatic diimine ligands and the corresponding homoleptic copper(i) and copper(ii) complexes have been synthesized and characterized. The copper(ii) derivatives are stabilized by an ancillary chlorido ligand. The nature of the chelating ligand seriously impacts the photophysical and electrochemical properties of the complexes. The substitution of the pendant methyl groups with methoxy influences the coordination geometry of the complexes, resulting in an intramolecular dynamic equilibrium between different coordination modes (i.e. nitrogen and oxygen binding), proved by variable-temperature H-1-NMR measurements. As a proof of concept, the most promising complexes were employed as redox mediators in semi-transparent dye-sensitized solar cells. Once implemented in devices, the nature of the ligand plays a crucial role: the methoxy-substituted derivatives appear upon severe ligand exchange with tert-butylpyridine, resulting in an unexpectedly high open circuit voltage.